Matching beef cattle breeds to the environment for desired outcomes in a changing climate: A systematic review. (April 2023) - McIntosh, Matthew M.; Spiegal, Sheri A.; McIntosh, Stacia Z.; Castaño Sanchez, José; Estell, Richard E.; Steele, Caitriana M.; Elias, Emile H.; Bailey, Derek W.; Brown, Joel R.; Cibils, Andrés F.
Abstract: Cattle graze approximately 30% of global land, making their interactions with Earth's social and ecological systems of critical importance. Cattle have experienced a long process of evolution and domestication. Certain breeds are more adapted to specific environments, differentially affecting those breeds' impact on the environment, their interaction with ecosystems experiencing climate change impacts, and their capacity to provide goods and landscape management services. Emerging evidence suggests that, compared to more artificially selected conventional breeds, some less specialized, or 'heritage' beef cattle breeds exhibit unique foraging behaviors that could support desired outcomes such as biodiversity or climate change adaptation. We provide a novel, systematic characterization of breed-based behavioral differences to assist researchers and beef producers in selecting breed-based management strategies for achieving adaptation goals. We conducted a systematic search of studies that compared beef cattle breeds for behavioral trends, and found 54 studies conducted between 1966 and present day, located in 9 of the 14 major terrestrial world biomes, with 60 beef or dual-purpose breeds represented. We created a typology of the studies with respect to decade, continent, breed provenance (Continental, Criollo, Hybrid, B. indicus, Mediterranean, Sanga, British Isles), breed selection intensity (heritage, conventional, hybrid), biome, study intent, and whether breeds met desired outcomes described by the study authors. Most studies (69%) were conducted in arid rangeland settings in developed nations where researchers sought to minimize the environmental impacts of beef production. In comparisons of grazing behavior of heritage versus conventional types ( n  = 25 studies), and hybrid versus conventional types ( n  = 18 studies), heritage and hybrid displayed more adapted traits (e.g., better grazing distribution) in 88% and 78% of the studies, respectively. No differences were found in grazing behaviors among most studies wherein heritage breeds were compared to other heritage breeds or conventional with conventional ( n  = 6 and 15 studies, respectively). In the subset of studies coded with the intent of "foraging behavior, " heritage types traveled faster across a range of pasture sizes, suggesting a lighter environmental footprint and adaptive capacity to heat impacts. Overall, our review suggests that locally derived breeds display grazing behaviors that demonstrate adaptation to their respective native environments and may help producers meet production goals in similar environments. We conclude that breeds with more natural selection tend to exhibit less rigid grazing behaviors, which is a necessary coping strategy in variable climates and locales with heterogeneous forage availability, both of which are increasingly common scenarios caused by climate change. Highlights: We identify breed-based behavioral differences among beef cattle to assist in achieving agroecosystem adaptation goals. Our systematic search revealed 54 studies from 9 terrestrial biomes, with 60 beef or dual-purpose breeds represented. Most studies were from arid rangelands where researchers sought to minimize the environmental impacts of beef production. Heritage and Hybrid cattle breeds displayed more adapted behaviors than Conventional counterparts. Locally derived breeds display grazing behaviors that demonstrate adaptation to their respective native environments.